2017
DOI: 10.1002/aelm.201700120
|View full text |Cite
|
Sign up to set email alerts
|

Diketopyrrolopyrrole‐Based Semiconducting Polymer with Both Hydrophobic Alkyl and Hydrophilic Tetraethylene Glycol Chains for Monolayer Transistor and Sensing Application

Abstract: studies also suggest that the first few layers of organic/polymeric semiconductors play key roles in determining the performances of FETs. [10][11][12][13][14][15] Moreover, downscaling the film thickness to a single molecular layer is of technological interest for the realization of bottomup electronic devices. [16][17][18] In particular, monolayer organic FETs (OFETs) are beneficial for sensing applications as the binding of the respective analytes with the semiconducting monolayer is expected to affect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…It was demonstrated that the TEG chain not only facilitated formation of a monolayer at the air-water interface, but also enabled selective detection of alcohol vapors. 60 The OFET based on a monolayer of PDPP3T1 responded to 10 ppb alcohols (isopropanol, ethanol or methanol) in the gas phase with a relative sensitivity over 2% ppb À1 , and was able to detect ethanol of concentration down to 1 ppb with good selectivity for alcohols over other gas molecules (CO 2 , hexane, CH 2 Cl 2 , acetone, and ethyl acetate), presumably due to the stronger interactions between TEG and alcohols through hydrogen bonds. Attachment of thermally reactive tert-butoxycarboxyl groups to the same poly(diketopyrrolopyrrole-terthiophene) backbone results in pDPPBu-BT ( Fig.…”
Section: Functionalization Of Individual Semiconductor Molecules Thromentioning
confidence: 98%
“…It was demonstrated that the TEG chain not only facilitated formation of a monolayer at the air-water interface, but also enabled selective detection of alcohol vapors. 60 The OFET based on a monolayer of PDPP3T1 responded to 10 ppb alcohols (isopropanol, ethanol or methanol) in the gas phase with a relative sensitivity over 2% ppb À1 , and was able to detect ethanol of concentration down to 1 ppb with good selectivity for alcohols over other gas molecules (CO 2 , hexane, CH 2 Cl 2 , acetone, and ethyl acetate), presumably due to the stronger interactions between TEG and alcohols through hydrogen bonds. Attachment of thermally reactive tert-butoxycarboxyl groups to the same poly(diketopyrrolopyrrole-terthiophene) backbone results in pDPPBu-BT ( Fig.…”
Section: Functionalization Of Individual Semiconductor Molecules Thromentioning
confidence: 98%
“…In the case of a bilayer configuration, the preferred elements will have (i) appreciable chemical compatibility among layers, (ii) good porous structures to improve gas absorption and (iii) good stability under various ambient conditions. Some of the strategies employed to realize better-sensing performance using DPP-based OFET sensors include optimization of film thickness, 16,17,20,38 tuning the porous structures to improve the surface reactivity, 18,20,39,40 blending the polymers with materials (such as graphene oxide, 39 MoS 2 , 39 polystyrenes, 39 PBA 39 and MOF 22 ) and attaching functional groups (sulfur-based motif, 41 siloxane, 39 butoxycarboxyl, 39 tetraethyl glycol, 16 thymine 42 and naphthalene 20 ) to the side chain of polymers. However, major disadvantages include their poor stability under humidity and bias stress and the resultant failure to exhibit reproducible and reliable gas-sensing performance.…”
Section: Detector Design and Operating Principlementioning
confidence: 99%
“…10,15 Diketopyrrolopyrrole-(DPP-)based CP semiconductors in particular are considered to be promising materials for sensing as a result of their tunable bandgap, good ambient stability, interactive functional groups and flexible electronic properties. [16][17][18][19][20][21][22] Furthermore, combining the versatile DPP molecules with rigid structures such as naphthalene, thiophene and their analogous moieties results in donor-acceptor (D-A) architectures with homogenous crystal stacking and strong pi-pi intermolecular interactions. 18,20,22 Recently, many research groups have successfully integrated the DPP-based D-A polymers on organic field-effect transistor (OFET) platforms to sense NH 3 , [23][24][25][26] NO 2 , [27][28][29] H 2 S 30,31 and various VOC molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Oligo‐ and polythiophenes, along with their derivatives, are an important class of fluorescent active organic semiconductors, owing to their conjugated structures. Therefore, they have been frequently studied for sensing, especially for fluorescence sensing . For the development of chemiresistors, oligothiophenes with well‐defined structures are preferred as candidates for the sensory materials because they possess at least the following two advantages: 1) high polarizability of sulfur electrons may provide a variety of intra‐ and intermolecular interactions, which are favorable for charge transport; and 2) easy modulation of chemical and physical properties through convenient structural modification .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they have been frequently studied for sensing,e specially for fluorescences ensing. [37][38][39][40][41] For the development of chemiresistors, oligothiophenes with well-defined structures are preferred as candidates fort he sensory materials because they possessa tl east the following two advantages: 1) high polarizability of sulfur electrons may provide av ariety of intra-and intermolecular interactions, which are favorable for charget ransport;a nd 2) easy modulation of chemical and physicalp roperties through convenient structural modification. [42][43][44] However,o ligothiophenes are photochemically and thermally unstable,w hich adds al imitation to their applications in opticalsensing.…”
Section: Introductionmentioning
confidence: 99%